In-situ co-design of Mobile Games using Design Thinking’s resources approach - Challiol, Cecilia; Borrelli, Franco Martín; Goin Plexevi, Francisco; Rouaux Servat, Candela Mariel; Mendiburu, Facundo Ivan; Gomez-Torres, Estevan; Gordillo, Silvia Ethel (Enfoque UTE, 2020)
The contribution of this paper is to explore how in-situ co-design of indoor spaces (e.g. building) of Location-based Mobile Games could be handle, by describing the learned lessons on this topic. This paper presents a conceptual framework for in-situ co-design of indoor spaces on Location-based Mobile Games to assist to carry out this kind of experience using useful resources (as Design Thinking's resources). An experience of in-situ co-design for an indoor space on a Location-based Mobile Game is presented using this framework; for some phases an authoring tool was used which allows in-situ co-design of relevant locations for an application. Based on this experience, the authoring tool was extended to create a specific kind of Location-based Mobile Game. This paper presents this extension along with a proof of concept that shows how an in-situ co-designed game created by this extension was used by end-users.